Financial globalization and environmental degradation nexus: Evidence from emerging economies - Ulucak, Zubeyde Senturk; Ilkay, Salih Cagri; Ozcan, Burcu; Gedikli, Ayfer (Elsevier Sci Ltd, 2020)
This study explores how financial globalization affects environmental degradation in the emerging economies by using ecological footprint as a proxy for environmental degradation. With this aim, panel data models are conducted for the annual data covering the period 1974-2016. Results indicated that there is not an inverted U-shaped relationship between economic growth and environmental degradation. It was also found that financial globalization contributes to the improvement of the environmental quality level of emerging economies.
Keywords: Financial globalization; Ecological footprint; Environmental Kuznets curve; PMG; DOLS